Notional defined contribution (NDC) pension schemes and income patterns - Sergio Nisticò; Mirko Bevilacqua (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
During the 1990s, some important European countries, particularly Italy and Sweden, have radically transformed their public pension system by adopting defined-contribution rules while retaining a pay-as-you-go financial architecture. This paper inquires into the theoretical properties of these Notional Defined Contribution pension schemes in order to identify the determinants of the replacement rates awarded to individuals with different income patterns. Three typical career patterns are taken into consideration, according to whether the individual wage growth is equal to, higher than, or lower than average wage growth. The impact of, and the possible remedies to, a possible discontinuity on the replacement rates is finally discussed by means of a sensitivity analysis of the replacement rates with respect to the career length (for a given retirement age), the retirement age, and the conventional rate of return credited on all individual accounts.
Keywords: H55; 330; NDC; replacement rates; income patterns